Eficiência da calda bordaleza e sulfocálcica em diferentes concentrações e idade de planta no controle de doenças foliares de maracujá-doce em cultivo orgânico - Ming, Lin Chau [UNESP]; Maia-Almeida, Chrystian Iezid [UNESP]; Marques, Marica Ortiz Mayo; Conceição, Danila Monte [UNESP]; Yuhara, Tiago [UNESP]; Leonel, Sarita [UNESP]; Tavares, Rodrigo de Castro; Silva, Joedna (My University, 2012)
The complex of leaves diseases that attack the culture of the passion fruit, especially, the sweet passion fruit (Passiflora alata) could commit the productivity and quality of fruits. However, P. alata, is also used as medicinal plant, being the leaves, the part used for this end. Then, the focus of the studies aiming to to agronomic management of P. alata for raw material production for pharmaceutical end, it diverges, at least partly, of the focus of the production of fruits. Therefore, it was evaluated the effect of bordaleza and sulfocálcica syrups in different concentrations and ages of plants on leaves diseases of P. alata. The experiment was installed in field conditions in randonmized blocks with five treatments and five repetitions of 10 plants each. The treatments were bordalesa syrup in 0,5 and 1,0%, sulfocálcica syrup in 0,5 and 1,0% prepared from main solution to 27th Baumé and the witness (without application). The treatment with sulfocalcica syrup in 0,5% promoted the smallest index of disease and the largest relative efficiency of control associated to the smallest rate of development of the disease with the age of the cultivation.

O complexo de doenças foliares que acometem a cultura do maracujá, em especial, a do maracujá-doce (Passiflora allata) comprometem a produtividade e qualidade de frutos e de suas superfícies fotossintética. Contudo, o P. allata, é utilizado também como medicinal, sendo as folhas, a parte utilizada para este fim. Desta forma, o enfoque de estudos voltados para o manejo agronômico do P. allata para produção de matéria prima para fim farmacêutico, diverge, pelo menos em parte, do enfoque da produção de frutos. Portanto, avaliou-se o efeito das caldas bordaleza e sulfocálcica em diferentes concentrações e idades de plantas sobre doenças causadoras de manchas foliares do P. allata. O experimento foi instalado em condições de campo em blocos ao acaso com cinco tratamentos e cinco repetições de 10 plantas cada. Os tratamentos foram: a) calda bordalesa a 0,5 e 1,0%; b) calda sulfocálcica a 0,5 e 1,0% a partir de solução matriz a 27º Baumé e c) testemunha (sem pulverização). O tratamento com calda sulfocalcica a 05 % promoveu o menor índice de doença e a maior eficiência relativa de controle associada à menor taxa de desenvolvimento da doença com a idade do cultivo.
The effect of bordaleza and sulfocálcica syrups in different concentrations and ages of plants on leafs diseases of sweet passion fruit in organic cropping
Keywords: Passiflora alata Dryander; Plant diseases control; Medicinal plants; Agroecological cropping; Passiflora allata Dryander; Droga vegetal; Fitossanidade; Plantas medicinais